2005
DOI: 10.1097/01.ju.0000173630.94559.fd
|View full text |Cite
|
Sign up to set email alerts
|

Combination Treatment With Propiverine Hydrochloride Plus Doxazosin Controlled Release Gastrointestinal Therapeutic System Formulation for Overactive Bladder and Coexisting Benign Prostatic Obstruction: A Prospective, Randomized, Controlled Multicenter Study

Abstract: This study reveals that combination therapy consisting of alpha1-adrenoceptor antagonists with antimuscarinics represents an effective and relatively safe treatment modality in select patients with OAB coexisting with benign prostatic obstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
102
2
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(109 citation statements)
references
References 15 publications
3
102
2
2
Order By: Relevance
“…Lee et al 25 observed that not only total IPSS but also patient satisfaction was better in the group with combination treatment rather than a-blocker monotherapy. However, the subtle divergence in the results of the Lee et al 25 study from those of the current trial is likely due, at least in part, to differences in study design. Both groups received active treatment Initial combined treatment for men with LUTS SH Lee et al (propiverine hydrochloride plus doxazosin GITS or doxazosin GITS only), and there was no placebocontrolled group.…”
Section: Initial Combined Treatment For Men With Luts Sh Lee Et Almentioning
confidence: 99%
“…Lee et al 25 observed that not only total IPSS but also patient satisfaction was better in the group with combination treatment rather than a-blocker monotherapy. However, the subtle divergence in the results of the Lee et al 25 study from those of the current trial is likely due, at least in part, to differences in study design. Both groups received active treatment Initial combined treatment for men with LUTS SH Lee et al (propiverine hydrochloride plus doxazosin GITS or doxazosin GITS only), and there was no placebocontrolled group.…”
Section: Initial Combined Treatment For Men With Luts Sh Lee Et Almentioning
confidence: 99%
“…The benefits of combination treatment with an a 1 -blocker and an antimuscarinic have been recognized over the last decade, supported by improved symptoms and quality of life reported in several large randomized trials [7][8][9][10][11][12][13] . Consequently, an a 1 -blocker in combination with an antimuscarinic is recommended for patients with moderate-to-severe LUTS/BPH if symptom relief is insufficient with monotherapy of either drug 1,4 .…”
Section: Introductionmentioning
confidence: 99%
“…In one study, tamsulosine and combination of tamsulosine and tolterodine were compared; Qmax improved in both groups but no significant difference was reported (19). In another study with 211 men, combination of doxazosin and propiverine was compared with doxazosin alone; after treatment, both groups were reported to have improved Qmax but there was no statistical difference between groups (20). One of the remarkable outcomes of our study was the statistically significant improvement of quality of life symptom scores.…”
Section: Discussionmentioning
confidence: 98%
“…Initially, Saito suggested the use of alpha blocker-antimuscarinic combination instead of (20). In another study, patients suffering from BOO (proven by pressure-flow urodynamic study) and BOO+OAB received doxazosin for 3 months.…”
Section: Discussionmentioning
confidence: 99%